2012
DOI: 10.1248/bpb.35.850
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Morphological Evidence for the Involvement of Glial Cells in the Antinociceptive Effect of Najanalgesin in a Rat Neuropathic Pain Model

Abstract: Neuropathic pain is a devastating neurological disease that seriously affects patients' quality of life. Despite a high level of incidence, the underlying mechanisms of neuropathic pain are still poorly understood. However, recent evidence supports the prominent role of spinal glial cells in neuropathic pain states. In our laboratory, we observed that najanalgesin, a novel peptide isolated from the venom of Naja naja atra, exerts significant analgesic effects on acute pain in mice and neuropathic pain in rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The cytokine TNFα is elevated in spinal cord of human inflammatory neuropathy (105). Such increases in TNFα are also found in nerve-ligated rats (111, 112). These findings support the role of inflammatory factors in chronic pain.…”
Section: Human Chronic Pain and Dynorphinmentioning
confidence: 61%
“…The cytokine TNFα is elevated in spinal cord of human inflammatory neuropathy (105). Such increases in TNFα are also found in nerve-ligated rats (111, 112). These findings support the role of inflammatory factors in chronic pain.…”
Section: Human Chronic Pain and Dynorphinmentioning
confidence: 61%
“…In the last 2 decades, stem cell transplantation has been considered a possible therapeutic method for the spinal cord injury and neuropathic pain conditions [6,[9][10][11][12][13]. Mesenchymal stem cells are the main source of cell therapy because of their ability of differentiating into multiple cell types, including blood, adipose tissue, connective tissues, osteocytes, chondrocytes, hepatocytes, myocytes, neurons, and cardiomyocytes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have observed that astrocytes were involved in the antinociception of najanalgesin during the maintenance of pain in the previous study. [ 7 ] Therefore, the effect of najanalgesin may act through the JNK signaling pathway in the spinal cord on the maintenance of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical sensitivity was assessed using the up-down method as previously described using a set of von Frey hairs (Ugo Basile, Italy). [ 6 7 ]…”
Section: Ethodsmentioning
confidence: 99%
See 1 more Smart Citation